EFEKTIVITAS KINERJA PEJABAT PENGADAAN BARANG JASA MELALUI E-PURCHASING TERHADAP SERAPAN ANGGARAN DI DINAS PENANAMAN MODAL PELAYANAN TERPADU SATU PINTU KABUPATEN BINTAN - Masjunaidi; Muhammad Imaaduddin (STAI Miftahul Ulum Tanjungpinang, 2024)
This study aims to find out the Performance Effectiveness of City Batang Officials through purchases at the One-Door Integrated Capital Investment Office of Bintan Regency. This study is a qualitative descriptive study, these studies are the 5 people who carry out procedures for procuring goods for services consisting of UKPBJ, Pokja, PPBJ, PPK and PPHP. Researchers use data collection techniques such as interviews, observations, and documentation. From the research results that can show that the Performance Effectiveness of Service Goods Acquisition Officials at the Servant Capital Planting Service One Door of Bintan Regency, if seen from the whole, is already felt. These results can be seen from quality, quality, time, cost, servant orientation, integrity, commitment, discipline and cooperation